Research Survey Distribution during the Pandemic: The ECF Platform Provider as an Authority of the Sender and using a Plea for Help - Siti Fatimah Mohd Kassim; Nurul Aini Muhamed (Human Resource Management Academic Research Society, 2024)
Vol. 13, No. 3, 2023, Pg. 989 – 1005